SOFT FUZZY DISCONNECTEDNESS IN DIMENSION THEORY - Vidhya, D.; Roja, E.; Uma, M.K. (Italian Journal of Pure and Applied Mathematics, 2015)
In this paper the concept of soft fuzzy B disconnected space is introduced and studied. In particular, soft fuzzy B disconnectedness via dimension theory is established.